The Philosophy of the Enlightenment as a Paradigm of Transhumanism - Markuckas, Marius (Problemos, 2020)
In the works devoted to the phenomenon of transhumanism, it is widely recognized that philosophy of the Enlightenment had a great intellectual influence on the formation of transhumanism. Yet, this article states that the ideas of Enlightenment philosophy can be reasonably treated as not only consisting the conceptual transhumanism core but also as being a source of its internal contradictions. The paper defends the position that transhumanism in general is an intrinsically controversial project and introduces the premises for this contradiction – the basic anthropological views inherited from philosophy of the Enlightenment. Finally, the article questions the status of transhumanism as a techno-scientific program and states it to be an ideologically engaged project in anthropological engineering, which, in its turn, is devoid of any clear theoretical and practical outline.